Design, implementation, and quality control in the Pathways American-Indian multicenter trial - Stone, Elaine J. (Prev Med, 2003)
BACKGROUND: Pathways was the first multicenter American-Indian school-based study to test the effectiveness of an obesity prevention program promoting healthy eating and physical activity. METHODS: Pathways employed a nested cohort design in which 41 schools were randomized to intervention or control conditions and students within these schools were followed as a cohort (1,704 third graders at baseline). The study’s primary endpoint was percent body fat. Secondary endpoints were levels of fat in school lunches; time spent in physical activity; and knowledge, attitudes, and behaviors regarding diet and exercise. Quality control (QC) included design of data management systems which provided standardization and quality assurance of data collection and processing. Data QC procedures at study centers included manuals of operation, training and certification, and monitoring of performance. Process evaluation was conducted to monitor dose and fidelity of the interventions. Registration and tracking systems were used for students and schools. RESULTS: No difference in mean percent body fat at fifth grade was found between the intervention and control schools. Percent of calories from fat and saturated fat in school lunches was significantly reduced in the intervention schools as was total energy intake from 24-hour recalls. Significant increases in self-reported physical activity levels and knowledge of healthy behaviors were found for the intervention school students. CONCLUSIONS: The Pathways study results provide evidence demonstrating the role schools can play in public health promotion. Its study design and QC systems and procedures provide useful models for other similar school based multi- or single-site studies.